Time-restricted feeding in rodent obesity models: impact on body weights, lipid profile and glucoregulation - Argaistieng, Joyce; Doraisamy, Bavani Visha; Halim, Hasseri; Syed Alwi, Sharifah Sakinah; Ali, Aida Azlina; Maniam, Sandra (Springer Nature, 2025)
Introduction: Dietary techniques such as time-restricted feeding (TRF) have received support in recent years due to their ability to improve metabolic health and prevent serious diseases. In scientific research, animal models are widely utilized to understand the physiological impacts of fasting and other dietary interventions, as they have similar physiology to humans. Several feeding windows ranging from 4 to 12 h have been reported in the literature. This review evaluates TRF protocols to determine the most effective feeding window for improving metabolic profiles. Methods: Several search keywords were utilized and only research articles published within the last fifteen years (2009–2024) were selected. Twelve studies were included in the final analysis to improve transparency. Results: Obesity was successfully induced within 6 weeks for 100% weight gain in C57BL/6 mice. The shortest duration of TRF intervention in mice is 6 weeks with 10 h of feeding. Meanwhile, induced obesity with 300% weight gain in Sprague-Dawley rats within 12 weeks. The shortest duration of TRF is 6 weeks with 8 h of feeding. Conclusion: TRF was consistently associated with reductions in body weight and total cholesterol, concomitant with an increase in glucose tolerance and insulin sensitivity in studies where these parameters were assessed. The most effective identified TRF regimen is a 10-h feeding window over 8 weeks in C57BL/6 mice. Future research on obesity may take into account the inclusion of different metabolic challenges to assess if the advantages of TRF are exclusive to any of the challenges or multiple challenges that contribute obesity. Limitations: A key limitation of this review is the heterogeneity in study protocols. The included studies varied in the duration of feeding hours (ranging from 4 to 12 h) using different rodent models.